2021
DOI: 10.1080/23311932.2021.1945281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rice variety and location on nutritional composition, physicochemical, cooking and functional properties of newly released upland rice varieties in Ethiopia

Abstract: The aim of this study was to characterize the newly released different upland rice varieties grown at two representative locations in Ethiopia. This experiment was conducted in factorial design arranged in completely randomized design with three replications. The factors considered were variety (Hidassie, Kokit, NERICA-3, NERICA-4, NERICA-12 and NERICA-13), and growing location (Fogera and Pawe). Collected samples were processed to brown rice and analyzed for selective physical, proximate, cooking, functional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
2
7
0
Order By: Relevance
“…The difference was significant (p˂0,05) between 60 and 80 ° C, Fofifa 159 had the highest rate, and from 80 ° C the swelling increased considerably. At 90 ° C the starch of the Fofifa 159 variety had a swelling power of 28.29 g of water / g of starch, which is slightly lower than the values found by Ashogbon and Akintao [21], during the study of upland rice starches from Nigeria with swelling values ranging from 24 to 32 g of water / g of starch at 95 ° C. Using other varieties, Lii et al [22] have found a swelling power ranging from 23 to 30g of water / g of starch at 95 ° C. Lower value have been reported by Abera et al [23] from popular varieties of upland rice from Ethiopia. Lii et al [22] have reported that rice starch having the lower amylose composition had a higher swelling power.…”
Section: Resultsmentioning
confidence: 70%
“…The difference was significant (p˂0,05) between 60 and 80 ° C, Fofifa 159 had the highest rate, and from 80 ° C the swelling increased considerably. At 90 ° C the starch of the Fofifa 159 variety had a swelling power of 28.29 g of water / g of starch, which is slightly lower than the values found by Ashogbon and Akintao [21], during the study of upland rice starches from Nigeria with swelling values ranging from 24 to 32 g of water / g of starch at 95 ° C. Using other varieties, Lii et al [22] have found a swelling power ranging from 23 to 30g of water / g of starch at 95 ° C. Lower value have been reported by Abera et al [23] from popular varieties of upland rice from Ethiopia. Lii et al [22] have reported that rice starch having the lower amylose composition had a higher swelling power.…”
Section: Resultsmentioning
confidence: 70%
“…More detailed information about NERICA-4 about other physio-morphological properties and chemical compositions could be found in Refs. [ 61 , 62 ]. The sample of NERICA-4 is shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In Ethiopia, most scientific information was published on the effect of parboiling conditions on rice's physical and cooking quality (Abera et al, 2021 ; Meresa et al, 2020 ). Nevertheless, there is a piece of limited scientific information on the optimization of conventional soaking time and temperature on the physicochemical properties of selected parboiled rice varieties (NERICA‐4 and NERICA‐6) grown in Eastern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%